2004
DOI: 10.1212/01.wnl.0000139301.01177.35
|View full text |Cite
|
Sign up to set email alerts
|

Driver route-following and safety errors in early Alzheimer disease

Abstract: Drivers with Alzheimer disease made more errors than neurologically normal drivers on a route-following task that placed demands on driver memory, attention, and perception. The demands of following route directions probably increased the cognitive load during driving, which might explain the higher number of safety errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 31 publications
7
149
0
1
Order By: Relevance
“…Because normal aging and age-related neurodegenerative conditions such as Alzheimer's disease affect multiple interacting aspects of cognition, we have been evaluating the validity of a composite index reflecting overall cognitive ability for the prediction of driver safety. The findings of this study and others (Rizzo et al, 2001;Uc et al, 2004) provide support for this approach. We anticipate that continued research in this vein will lead to a brief (less than 15 minutes), standardized, inexpensive cognitive screening battery, with automated scoring algorithms and empirically-derived cutoff scores, that will provide a fair and efficacious means of determining driver safety.…”
Section: Figure 2 the Curves According To Cft-recall Scoresupporting
confidence: 79%
See 1 more Smart Citation
“…Because normal aging and age-related neurodegenerative conditions such as Alzheimer's disease affect multiple interacting aspects of cognition, we have been evaluating the validity of a composite index reflecting overall cognitive ability for the prediction of driver safety. The findings of this study and others (Rizzo et al, 2001;Uc et al, 2004) provide support for this approach. We anticipate that continued research in this vein will lead to a brief (less than 15 minutes), standardized, inexpensive cognitive screening battery, with automated scoring algorithms and empirically-derived cutoff scores, that will provide a fair and efficacious means of determining driver safety.…”
Section: Figure 2 the Curves According To Cft-recall Scoresupporting
confidence: 79%
“…Difficulties with episodic memory are common in many neurologic conditions, and may dissociate from relatively preserved procedural or motor memory. Such deficits appear to impact most strongly on certain aspects of driving, such as route-following, while preserved procedural memory abilities allow for generally good vehicle control (Anderson et al, 2005;Cavaco et al, 2004;Uc et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a category fluency task was predictive of simulated driving performance in patients with Alzheimer's disease (AD) (Rebok et al, 1994), and the Controlled Oral Word Association Test (COWA) was a predictor of on-road driving performance in patients with early AD (Uc et al, 2004). However, the Word Fluency Test (Duchek et al, 1998;Hunt et al, 1993) for phonemic association and Generative Naming (Whelihan et al, 2005) for semantic association were not related to on-road driving performance in patients with early cognitive decline or AD.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that selective deficits of visual motion processing in AD and MCI are associated with disorders of ambulatory and vehicular navigation. 2,9,10 These impairments lead to getting lost and accidental collisions while driving, 11,12 as well as wandering and the loss of independent living. 13,14 We have previously characterized navigational disorders in AD using a standardized real-world test environment, identifying task and subject variables that influence navigational strategies and navigational success.…”
mentioning
confidence: 99%